MODEL PENGGUNAAN LAHAN UNTUK BANGUNAN DI WILAYAH TRANSISI PROVINSI BALI - Sudipta, I Gusti Ketut; Adnyana Putera, IGA.; Suparsa, I Gusti Putu (Jurnal Ilmiah Teknik Sipil; Vol. 13, No. 1 Januari 2009)
The growth of land use for building in Bali Province may pose problems in the foreseeable future. The primary objective of this research is to assess the relation of the land use area for the building against time in the period to come, how long the land could support the growth of the land use for building and to identify the regulating method of the land use for building in transitional territory of Bali Province in order to be able to sustain long term growth. The research data consisted of the area of the settlement, tourism and cultivation zones that were obtained from The Revised Map of The Bali Province Spatial Planning 2003. The rest of the research data consisted of buildings number and land user in form of data series that were obtained through documents registration technique. Results of the analysis showed that the forecast annual growth of land use for building in transitional territory of Bali Province was 2.32%; the settlement zone could only support the growth of the land use for the building up until 2013; the tourism zone could support the growth for much longer time; the cultivation zone will be fully used in 2072; efforts so that the land could support the growth of the land use for building longer in transitional territory of Bali Province were to reduce population growth or to reduce land use area designated per 1 building user.
Keywords: land use, building, transitional territory, Bali, model.